2015
DOI: 10.1155/2015/943821
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Characterization, and Antibacterial Activity of Silver/Polystyrene Nanocomposite

Abstract: A novel, nontoxic, simple, cost-effective and ecofriendly technique was used to synthesize green silver nanoparticles (AgNPs). The AgNPs were synthesized using orange peel extract as a reducing agent for silver nitrate salt (AgNO 3 ). The particle size distribution of AgNPs was determined by Dynamic Light Scattering (DLS). The average size of silver nanoparticles was 98.43 nm. The stable dispersion of silver nanoparticles was added slowly to polystyrene solution in toluene maintaining the temperature at 70 ∘ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Our results are supported by different reported studies with sharp peaks at 3 keV in EDX (34)(35)(36)(37). As these AgNPs were synthesized with different plant materials, Acacia nilotica, Citrus sinensis, Cosmos Sulphureus, and Dracocephalum moldavica, still the resultant Ag availability was determined at around 3 keV through EDX analysis.…”
Section: Edx Detectionsupporting
confidence: 92%
“…Our results are supported by different reported studies with sharp peaks at 3 keV in EDX (34)(35)(36)(37). As these AgNPs were synthesized with different plant materials, Acacia nilotica, Citrus sinensis, Cosmos Sulphureus, and Dracocephalum moldavica, still the resultant Ag availability was determined at around 3 keV through EDX analysis.…”
Section: Edx Detectionsupporting
confidence: 92%
“…4b, broad and intensified peak at 3421.92 cm −1 indicated the O-H group stretching of phenolic group present in the orange leaf extract. Sharp peaks at 1642 and 1598 cm −1 were due to C = C stretching, this group must be present in flavonoids and monoterpenes (Awad et al 2014) and amide group in proteins. Peak at 1085 and 1047.57 cm −1 indicated C-O stretching in primary and secondary alcohols, respectively (Khalil 2014).…”
Section: Ft-irmentioning
confidence: 96%
“…The amorphous halo was caused by the spacing of individual polymer chains. Comparison of the diffraction patterns of PMMA and greener AgNP/PMMA nanocomposite showed that the peaks corresponding to PMMA became broader and seemed to disappear because of small AgNPs embedded in the PMMA chains [26].…”
Section: And 3(b)mentioning
confidence: 99%
“…International Journal of Polymer Science AgNP/polymer nanocomposite film is valuable in many industrial applications. The technique permits the utilization of a nontoxic, cheap, ecofriendly, bioavailable material [26].…”
mentioning
confidence: 99%